PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SQUARE TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS VIII SMPN 29 PADANG - Listari, Yumi Fardila; Elniati, Sri (Jurnal Edukasi dan Penelitian Matematika, 2024)
In learning mathematics, mathematical communication is crucial for students. However, currently the ability of students in class VIII of SMPN 29 Padang is not good in mathematical communication. The Think Pair Square (TPSq) cooperative learning model can overcome this problem. This research compares the mathematical communication skills of students who applied the TPSq approach with conventional learning. This research is a pseudo-experiment through Nonequivalent Posttest-Only Control Group Design. The results proved that students who applied the TPSq model had higher mathematical communication skills compared to conventional learning.Keywords: Mathematical Communication Skills, Cooperative Learning, Think Pair Sqaure, Conventional Learning